2018
DOI: 10.1590/1678-5150-pvb-5533
|View full text |Cite
|
Sign up to set email alerts
|

Esteatose hepática altera acúmulo celular em tilápias do Nilo durante aerocistite infecciosa

Abstract: RESUMO: O presente estudo avaliou a hepatotoxicidade induzida pelo CCl4 durante o efeito glicocorticoide da dexametasona (DEX) na fisiopatologia da reação inflamatória aguda em tilápias do Nilo, Oreochromis niloticus, correlacionando a funcionalidade hepática à cinética de acúmulo celular em aerocistite infecciosa. Para tal, utilizou-se 84 tilápias do Nilo distribuídas em 4 tratamentos: controle, CCl4, DEX e CCl4+DEX. Sendo amostrados 7 animais por tratamento em três períodos, isto é: seis, 24 e 48h após induç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The increase in the metabolic degradation of the drug in hepatocytes can result in the production of free radicals that favor the increase of lipid peroxidation and consequently changes in the permeability of the hepatocyte plasma membrane, which can result in extravasation of this enzyme, as well as in the most severe cases cause cytotoxicity (Moraes et al, 2018;Oliveira et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the metabolic degradation of the drug in hepatocytes can result in the production of free radicals that favor the increase of lipid peroxidation and consequently changes in the permeability of the hepatocyte plasma membrane, which can result in extravasation of this enzyme, as well as in the most severe cases cause cytotoxicity (Moraes et al, 2018;Oliveira et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effect of astaxanthin resulted in a decrease in the number of thrombocytes and leukocytes in tilapias, marked by a decrease in the number of lymphocytes and neutrophils. These results suggest the hypothesis that fish supplemented with astaxanthin had a better leukocyte response, since modulation in circulating levels of white blood cells usually occurs during inflammatory defense responses (Moraes et al, 2018;Prado et al 2018). Belo et al (2014) observed a similar effect with improved leukocyte response in pacus supplemented with vitamin E during foreign body inflammatory reaction.…”
Section: Discussionmentioning
confidence: 73%
“…As tilapia is a species with high popularity and the second most farmed fish species globally (Islam, Rohani, & Shahjahan, 2021), the maximal use of the animal is desirable. According to Moraes et al (2018), waste of fishing (head, entrails, skin, and dorsal spine) may represent 62.5% animal weight and cause environmental contamination. Thus, the lower the weight of viscera, the better the use by the animal.…”
Section: Animal Performancementioning
confidence: 99%